Fitness test profiles in children aged 8-12 years old in Granada (Spain) - López García, Ricardo; Cepero González, Mar; Suárez Llorca, Concepción; Andreu Cabrera, Eliseo; Rojas Ruiz, Francisco Javier (2011)
The aim of this study was to determine the effects of physical education in body composition and health-related fitness among boys and girls aged 8 to 12 years old in Granada (Spain) in a longitudinal, randomized study of 5 months. 106 children (49 boys and 57 girls) between 8 and 12 years old completed the study. They were healthy students of the public schools and no history of formal exercise training. Subjects were tested (body composition and health-related fitness, measured by EUROFIT) at baseline and at week 20. After 5 months of study, girls showed more fat mass than boys (p<0.05) and boys was more height than girls (p<0.05). Health-related fitness showed differences by gender only in slalom (boys vs. girls (p<0.05)). The results of body composition and health-related fitness revealed that the physical activity at school is not sufficient to support an ideal level of health-related fitness.